Average Error: 0.0 → 0.0
Time: 11.7s
Precision: 64
\[{2}^{x} - {x}^{1}\]
\[{2}^{x} - {x}^{1}\]
{2}^{x} - {x}^{1}
{2}^{x} - {x}^{1}
double f(double x) {
        double r20727354 = 2.0;
        double r20727355 = x;
        double r20727356 = pow(r20727354, r20727355);
        double r20727357 = 1.0;
        double r20727358 = pow(r20727355, r20727357);
        double r20727359 = r20727356 - r20727358;
        return r20727359;
}

double f(double x) {
        double r20727360 = 2.0;
        double r20727361 = x;
        double r20727362 = pow(r20727360, r20727361);
        double r20727363 = 1.0;
        double r20727364 = pow(r20727361, r20727363);
        double r20727365 = r20727362 - r20727364;
        return r20727365;
}

Error

Bits error versus x

Try it out

Your Program's Arguments

Results

Enter valid numbers for all inputs

Derivation

  1. Initial program 0.0

    \[{2}^{x} - {x}^{1}\]
  2. Final simplification0.0

    \[\leadsto {2}^{x} - {x}^{1}\]

Reproduce

herbie shell --seed 1 
(FPCore (x)
  :name "pow(2,x)-pow(x,1)"
  (- (pow 2.0 x) (pow x 1.0)))